Fig 3 in Helminth Diversity In Teleost Fishes From The South Orkney Islands Region, West Antarctica ... - Kuzmina, T. A.; Salganskiy, O. O.; Vishnyakova, K. O.; Ivanchikova, J.; Lisitsyna, O. I.; Korol, E. M.; Kuzmin, Yu. I. (Zenodo, 2022)
Fig 3. Cluster analysis of the similarity between the helminth communities of the shallow-water (SW) and deepwater (DW) populations of fish species determined by the Bray-Curtis index. ... : Published as part of Kuzmina, T. A., Salganskiy, O. O., Vishnyakova, K. O., Ivanchikova, J., Lisitsyna, O. I., Korol, E. M. & Kuzmin, Yu. I., 2022, Helminth Diversity In Teleost Fishes From The South Orkney Islands Region, West Antarctica, pp. 135-152 in Zoodiversity 56 (2) on page 144, DOI: 10.15407/zoo2022.02.135, http://zenodo.org/record/7175665 ...